Unfavorable Changes of Platelet Reactivity on Clopidogrel Therapy Assessed by Impedance Aggregometry Affect a Larger Volume of Acute Ischemic Lesions in Stroke - Wiśniewski, Adam; Sikora, Joanna; Karczmarska-Wódzka, Aleksandra; Sobczak, Przemysław; Lemanowicz, Adam; Zawada, Elżbieta; Masiliūnas, Rytis; Jatužis, Dalius (Diagnostics (Basel), 2021)
Background: High on-treatment platelet reactivity or its equivalent—resistance to the antiplatelet agent—significantly reduces the efficacy of the therapy, contributing to a negative impact on stroke course. Previous studies demonstrated that aspirin resistance is associated with a larger size of acute ischemic infarct. Due to the increasing use of clopidogrel in the secondary prevention of stroke, we aimed to assess the impact of clopidogrel resistance on the size and extent of ischemic lesions, both acute and chronic. Methods: This prospective, single-center and observational study involved 74 ischemic stroke subjects, treated with 75 mg of clopidogrel. We used impedance aggregometry to determine platelet reactivity 6–12 h after a dose of clopidogrel as a first assessment and 48 h later as the second measurement. A favorable dynamics of platelet reactivity over time was the decrease in the minimum value equal to the median in the entire study. The volume of acute ischemic infarct was estimated within 48 h after onset in diffusion-weighted imaging and fluid-attenuated inversion recovery sequences of magnetic resonance and the severity of chronic vascular lesions by Fazekas scale. Results: Subjects with mild severity of chronic vascular lesions (Fazekas 1) exhibited a significant decrease of platelet reactivity over time (p = 0.035). Dynamics of platelet reactivity over time differed between subjects with large, moderate, mild and insignificant size of acute ischemic lesion (Kruskall-Wallis H = 3.2576; p = 0.048). In multivariate regression models, we reported unfavorable dynamics of platelet reactivity alone and combined with a high initial value of platelet reactivity as independent predictors of higher risk of a significant ischemic infarct volume (OR 7.16 95%CI 1.69–30.31, p = 0.008 and 26.49 95%CI 1.88–372.4, p = 0.015, respectively). Conclusions: We emphasized that unfavorable dynamics of platelet reactivity over time during clopidogrel therapy in acute phase of stroke affect the volume of acute infarct and the severity of chronic vascular lesions.